Genomic imprinting in mouse blastocysts is predominantly associated with H3K27me3 - Santini, Laura (Nat Commun, 2021)
In mammalian genomes, differentially methylated regions (DMRs) and histone marks including trimethylation of histone 3 lysine 27 (H3K27me3) at imprinted genes are asymmetrically inherited to control parentally-biased gene expression. However, neither parent-of-origin-specific transcription nor imprints have been comprehensively mapped at the blastocyst stage of preimplantation development. Here, we address this by integrating transcriptomic and epigenomic approaches in mouse preimplantation embryos. We find that seventy-one genes exhibit previously unreported parent-of-origin-specific expression in blastocysts (nBiX: novel blastocyst-imprinted expressed). Uniparental expression of nBiX genes disappears soon after implantation. Micro-whole-genome bisulfite sequencing (µWGBS) of individual uniparental blastocysts detects 859 DMRs. We further find that 16% of nBiX genes are associated with a DMR, whereas most are associated with parentally-biased H3K27me3, suggesting a role for Polycomb-mediated imprinting in blastocysts. nBiX genes are clustered: five clusters contained at least one published imprinted gene, and five clusters exclusively contained nBiX genes. These data suggest that early development undergoes a complex program of stage-specific imprinting involving different tiers of regulation.